Rancang Bangun Modul Pembelajaran High Pass Filter dan Low Pass Filter untuk Praktikum di Laboratorium Teknik Telekomunikasi Politeknik Negeri Sriwijaya - Zefi, Susan; Ciksadan, Ciksadan; Alifah, Farah Balqis; Shalama, Maura Fatima (Journal of Science and Engineering, 2024)
Filters are one of the series that are needed in everyday life. Both in the fields of electronics and telecommunications.This circuit is composed of passive components, namely resistors and capacitors. The research method used is the experimental method for the module design stage which will be tested and prove the output results based on theory. Based on data from experiments that have been carried out, the passive second order high pass filter and low pass filter circuit produces the same frequency response as the theory, namely when the circuit is given a voltage of 1V and a different frequency, it produces the frequency response graph increases where the higher the frequency, the higher and more stable the frequency response graph produced vice versa. According to the data that has been obtained and converted to a frequency response graph, it proves that the frequency response graph of the module made is almost the same as the frequency response graph of the CET-17202B-01 module, only there is a slight difference in the output voltage and tolerance due to the influence of the load on the components used.Â